Ecotourism site suitability evaluation using geospatial technologies: a case of Andiracha district, Ethiopia - Ambecha, Andualem Befekadu; Melka, Girma Alemu; Gemeda, Dessalegn Obsi (Spatial information research (Online), 2020)
This study is aimed to identify potential ecotourism sites using Geographic Information System and Multi-criteria Decision Analysis in Adiracha district of Sheka Zone, south-western Ethiopia. Landsat ETM Image and STRM data of 2016 with 30 m resolution and topographic map of Ethiopia were used in this study. Ecotourism potential site selection criteria were designed based on 26 stakeholder’s opinions. The final suitability map of ecotourism has been realized by applying an integrated weighted overlay technique of Geographic Information System. The suitability map was categorized into four classes as Suitable, Moderately Suitable, Less Suitable, and Not Suitable. The study attempts to indicate the level of ecotourism suitability at different location in the study area. The outcome of this research is useful to understand the spatial information of Sheka district that can be used for policy makers. This study can be also used as a basis for assessing ecotourism site suitability in other regions.